Análisis termodinámico y cinética de reacción del proceso de gasificación de raquis de palma para la cogeneración de energía eléctrica y calor. (2022)
The first phase of the project corresponds to the physicochemical characterization of the palm rachis, through a bibliographic review, where it is identified that the palm rachis has a high energy potential, due to its high percentage of volatile material. Following this, the project includes the proposal of two process schemes, the first contemplating an open gas cycle and the second a closed gas cycle, as well as the development of a PFD diagram. As the next phase of the project, the kinetic model is carried out, developing the calculation equations by means of an analytical method, and identifying the kinetic parameters of the selected reactions, obtaining as a result that the composition of the synthesis gas is as follows, 48% for CO, 0.019% for CO2 and 6.71% for H2. The thermodynamic analysis of this project is based on the results of the kinetic model, implementing the Coolprop computational tool to calculate the thermodynamic properties of the currents of the two proposed process schemes. In accordance with the above according to the results obtained, the substance R134a is selected for the first scheme and propane for the second scheme. A comparative analysis of the results obtained with respect to those available in the literature is performed. The project contemplates a cost analysis, according to the selected equipment, to evaluate a possible decrease in the costs of electrical energy in the palm oil extraction plants and consequently promote renewable energy alternatives in the Colombian palm industry.